Karir dalam Organisasi Selular (Career in Celullar Organizations) - Fransiska Soejono (Jurnal Manajemen Maranatha, 2007)
This article explains about the existence of organizational evolution and the existence of career development. Organizational nowadays matching with a global conditions these days is cellular organization, while in recognized by boundaryless career of existence of an career protean. In career protean, career change influenced by change the assess, importance, and individual ability. Specific competence required to reach the success in the twenty first century organization. The change that happened in organizations will influence the individuals who exist in the organizations. Creative individual will exploit the change that happened to reach the career efficacy. A lot of problem which are possible happened because the change in organizations and also in growth of career of twenty first century. That‟s why it needed some consideration and effectivity in career management.